PROFIL PENYULUHAN PERTANIAN DI PROVINSI LAMPUNG SEJAK DIGULIRKANNYA OTONOMI DAERAH DAN HUBUNGANNYA DENGAN REVITALISASI PENYULUHAN PERTANIAN - Gs, Sumaryo (Lampung University)
Since autonomy era, each province or regency have a different institution of agricultural extension. The fact influences to the implementation of agricultural extension on farmers. The program and organization of agricultural extension must be revitalized in order to support the national agricultural development. This study describes agricultural extension profile and that institution. This study also analyzes issues and factors on revitalization of agricultural extension, especially in Lampung Province.Â Descriptive analysis is employed in this study. The result show that Â to anticipate the next political and socio-economic changes, there are six factors must be handled; (a) agricultural extension and agricultural development policy, (b) agricultural extension clients, (c) organization and management of agricultural extension, (d) program, strategy, and method of extension, (e) human resource of agricultural extension workers, and (f) financial resource of extension programs.